The livestock production systems in three peasant associations of the Awassa Woreda - Alemayehu, Y.; Tegegne, Azage; Kurtu, M.Y. (Ethiopian Society of Animal Production, 2000)
A diagnostic survey of the general livestock production system was conducted in three associations of the Awassa Woreda from June 1997 up to May. 1998. Purposive and random sampling techniques were used in the selection of the 3 peasant associations and 30 farmers per peasant associations, in respective order. The private and communal grazing land was about 16.6 and 41 4 ha, respectively. Feed supply of 75.4, 496.3, 24.7 and 15 t DM per were estimated from natural grazing pastures, major crop residues (maize stover, wheat straw, barley staw, and enset pseudo-stems and leaves), forage trees/shrubs, and from other feed sources (grains, nug cake, cut grass/weeds and stubble grazing), respectively. The overall DM from different feed sources was calculated to be 611.4 t per year. The livestock biomass held by the 90 respondents was estimated at 419 TLU. The available feed was also estimated about 611.4 t per year while the requirement was 917.8 t DM. Similarly the DP requirement was estimated to be 32.1 t while the supply was 25.5 t DM. Therefore, the available feed felt to cover by 33.4 and 20:6 % of their energy and protein requirements, respectively. About 218.3, 165.8 and 202.5 t DM were estimated to be available during small, medium and big rainfall seasons, respectively. The overall feed potential was relatively higher during the big rainfall season and least was during the long small rainfall season. The livestock management system was predominantly traditional. All classes and species of animals were herded together. The allocation of feed based on the level of production was very much limited but a certain degree of prioritization for cows (when they were milked) followed by work-oxen (during the cultivation period or from February to March) was observed.